Writing Strategies for All Primary Students : Scaffolding Independent Writing with Differentiated Mini-Lessons, Grades K-3 - Richards, Janet C., 1936-; Lassonde, Cynthia A., 1957- (San Francisco, CA : Jossey-Bass, 2011)
'A guide for teaching all your students the skills they need to be successful writers The 25 mini-lessons provided in this book are designed to develop students' self-regulated writing behaviors and enhance their self-perceived writing abilities. These foundational writing strategies are applicable and adaptable to all primary students: emergent, advanced, English Language Learners, and struggling writers. Following the SCAMPER (Screen and assess, Confer, Assemble materials, Model, Practice, Execute, Reflect) mini-lesson model devised by the authors, the activities show teachers how to scaffold the writing strategies that students need in order to take control of their independent writing. {u04A5}veals helpful writing strategies, including making associations, planning, visualizing, accessing cues, using mnemonics, and more {u03E6}fers ideas for helping students revise, check, and monitor their writing assignments Ÿplains the author's proven SCAMPER model that is appropriate for students in grades K-3 Let Richards and Lassonde--two experts in the field of childhood education--guide you through these proven strategies for enhancing young children's writing skills'--
Includes bibliographical references and indexes.
Keywords: Composition (Language arts) -- Study and teaching (Primary); English language -- Composition and exercises